National economic security of the state in the context of globalization - Айтбембетова A.; Алтынбекова, Г. (Journal of Economic Research & Business Administration, 2017)
At the end of XX century of the term “national economic security” became important in management of the country. National economic security – is a stability of the country both internal and external threats, also when country can provide stability of economy and develop providing demands of the people living in this country. Stability and sustainability of national economy reveals the strength of economic system, security from different unforeseen factors. For this reason countries develop economic security. The indicators reflecting a condition of the country in general such as inflation, unemployment rate, Jeanie’s coefficient and the part of the population with the below a living wage and so on are vast important for economic security. The article reveals the general concept of economic security, the analysis of its’ main indicators, also in the article are provided the ways of development of Kazakhstan.